Path Planning Control for Mobile Robot - Abid Al- Sahib, Nabeel K.; Salih, Amenah A.H. (Al-Khwarizmi Engineering Journal, 2011)
Autonomous motion planning is important area of robotics research. This type of planning relieves human operator from tedious job of motion planning. This reduces the possibility of human error and increase efficiency of whole process. This research presents a new algorithm to plan path for autonomous mobile robot based on image processing techniques by using wireless camera that provides the desired image for the unknown environment . The proposed algorithm is applied on this image to obtain a optimal path for the robot. It is based on the observation and analysis of the obstacles that lying in the straight path between the start and the goal point by detecting these obstacles, analyzing and studying their shapes, positions and points of intersection with the straight path to find the nearly optimal path which connects the start and the goal point. This work has theoretical part and experimental part. The theoretical part includes building a MATLAB program which is applied to environment image to find the nearly optimal path .MATLAB - C++.NET interface is accomplished then to supply the path information for C++.NET program which is done for programming the pioneer mobile robot to achieve the desired path. The experimental part includes using wireless camera that takes an image for the environment and send it to the computer which processes this image and sends ( by wireless connection ) the resulted path information to robot which programmed in C++.NET program to walk according to this path. So, the overall system can be represented by: Wireless camera – computer – wireless connection for the mobile robot . The experimental work including some experiments shows that the developed mobile robot (pioneer p3-dx ) travels successfully from the start point and reach the goal point across the optimal path (according to time and power) which is obtained as result of the proposed path planning algorithm introduced in this paper.